From over to optimal irrigation in paddy production: What determines over-irrigation in Bangladesh? - Islam, Md. Sariful; Tumpa, Shamshunnahar; Afrin, Sonia; Ahsan, Md. Nasif; Haider, Mohammed Ziaul; Das, Debasish Kumar (Springer Link, 2022)
This article was published in Sustainable Water Resources Management [©2012 Published the Author(s), under exclusive license to Springer Nature Switzerland AG] and the definite version is available at: https://doi.org/10.1007/s40899-021-00512-0 The Article's website is at: https://link.springer.com/article/10.1007/s40899-021-00512-0#citeas